Nine ways to score nine lives – identifying appropriate methods to age domestic cats (Felis catus). (6th March 2021) - Fleming, Patricia A.; Crawford, Heather M.; Auckland, Clare; Calver, Michael C.
Abstract: Accurate determination of chronological age for cats ( Felis catus ) permits assessment of age at reproduction and growth measures, whilst understanding survivorship enables modelling of population dynamics underpinning many management questions. At present, the relative accuracy of different measures has not been compared, especially in relation to ageing live cats, where options are more limited. We tested relationships between nine ageing methods using a large database of 384 unowned, free‐roaming cats culled as part of wildlife conservation and unowned cat management. Cat heads were cleaned and scored for tooth eruption, development of the canines (root closure, length and width; proportion of pulp determined by radiography), canine tooth cementum lines, tooth wear (canine tip sharpness and breakage, or absence of the P 2 ), diastema distance and closure of two cranial sutures. Tooth eruption is informative for cats up to about 8 months of age and closure of the canine root up to 12 months. In adults with closed‐rooted canine teeth, only the cementum lines and cranial sutures varied; these two sets of measures were strongly correlated. We conclude by developing a predictive table for ageing cat specimens using tooth and skull features. Animals can be aged reliably over the lifespan of the animal from cadaver material, potentially adding valuable information to ecological studies where cats are culled. However, there is no way to reliably age live cats over approximately 8 months of age in the field, after which time full adult dentition is established. Similarly, radiography (to determine pulp volume) has limited use as an ageing tool for cats older than 1–2 years of age. This reduces the number of potential applications for live cats, including, for example, ageing unowned cats in trap–neuter–release programmes. Abstract : Accurate determination of chronological age for cats ( Felis catus ) permits assessment of age at reproduction and growth measures, whilst understanding survivorship enables modelling of population dynamics underpinning many management questions.